2016
DOI: 10.1021/acsami.6b02994
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Polydopamine Functionalized Coiled Microfibrous Scaffolds Enhance Human Mesenchymal Stem Cells Colonization and Mild Myofibroblastic Differentiation

Abstract: Electrospinning has been widely applied for tissue engineering due to its versatility of fabricating extracellular matrix (ECM) mimicking fibrillar scaffolds. Yet there are still challenges such as that these two-dimensional (2D) tightly packed, hydrophobic fibers often hinder cell infiltration and cell-scaffold integration. In this study, polycaprolactone (PCL) was electrospun into a grounded coagulation bath collector, resulting in 3D coiled microfibers with in situ surface functionalization with hydrophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 74 publications
2
63
1
Order By: Relevance
“…However, mechanism of the interactions and accurate structures of PDA had not been confirmed yet . The formed PDA can further incorporate many functional groups, such as phenol, amine, thiol and imine groups . Polymers (or tissues) containing these functional groups can react with PDA via hydrogen bonds and covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…However, mechanism of the interactions and accurate structures of PDA had not been confirmed yet . The formed PDA can further incorporate many functional groups, such as phenol, amine, thiol and imine groups . Polymers (or tissues) containing these functional groups can react with PDA via hydrogen bonds and covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for preparing 3D electrospun nanofibrous scaffolds and the microscopic morphology: (a) sacrificial components (Wang et al, ); (b) wet‐electrospinning (Chakrapani, Kumar, Raj, & Kumary, ; Taskin et al, ); (c) cryogenic electrospinning (Formica et al, ); (d) electrohydrodynamic printing (Wu et al, ); (e) dispersion‐shaping (Xu, Miszuk, Zhao, Sun, & Fong, ); (f) gas‐foaming (Hwang et al, )…”
Section: Fabrication Of 3d Nanofibrous Scaffoldsmentioning
confidence: 99%
“…Mehmet et al developed a 3D PCL nanofibrous scaffold by wet electrospinning. For polydopamine coating, the PCL solution was spun on a 95% ethanol bath containing 1 mM NaOH and 5 mg/ml dopamine (Taskin et al, ). Similarly, by polydopamine coating, BMP‐2 derived peptides can also be adsorbed onto the surface of scaffold without inactivation and sustained release for more than 20 days (Ye et al, ).…”
Section: Biomodification Of 3d Nanofibrous Scaffoldsmentioning
confidence: 99%
“…pDA coated fibers were found to enhance osteogenesis of bone marrow stem cells, suggesting its role in commitment of MSCs toward osteogenic lineage. Another study showed the multi‐walled carbon nanotube coating on polycaprolactone fibers enhanced cell adhesion and proliferation for nerve tissue regeneration . Hence, surface functionalization of electrospun fibers provides an environment which is more favorable for cells to interact with the substrate.…”
Section: Factors Effecting Cell Adhesion and Proliferationmentioning
confidence: 99%
“…Another study showed the multi-walled carbon nanotube coating on polycaprolactone fibers enhanced cell adhesion and proliferation for nerve tissue regeneration. [23] Hence, surface functionalization of electrospun fibers provides an environment which is more favorable for cells to interact with the substrate. Identification of the required functional groups and surface coating for the electrospun fibers is a crucial parameter to make the substrate more biocompatible.…”
Section: Surface Coating/functionalizationmentioning
confidence: 99%